Le geografie oscillanti: Mappe etiche e mappe cartografiche nell’opera di Antonella Anedda (TEST Ticontre. Theory Text Translation, 2026)
The article analyzes the relationship between geography, writing, and ethics in the work of Antonella Anedda, adopting a geocritical and geopoetic approach. Through close readings of both poetry and prose (in particular Isolatria, Geografie, Notti di pace occidentale, and Historiae), it highlights how maps and borders are not mere backdrops or themes, but formal and narrative devices that articulate an oscillating perspective between the inside and outside, individual and collective, past and present. The map becomes a means of relating the self to the world, while the border is constantly challenged. Anedda’s writing, hybrid in both form and perspective, constructs an ethical space in which geography is grounded in a network of relationships, also including a reflection on media and the relationship between human beings and the environment.